Low-frequency laboratory measurements of the acoustic parameters of Savonnieres limestone - Mikhaltsevitch, Vassili; Gurevich, Boris; Lebedev, Maxim (SEG, 2014)
A significant portion of the world's hydrocarbon reserves are found in carbonate reservoirs, but analysis of the petrophysical properties of these reservoirs is associated with a number of problems stemmed from the fact that physical and chemical interactions taking place between a carbonate rock and pore fluids affect the elastic parameters of the rock matrix. A study of the pore fluid effects on the acoustic properties of carbonates is important for understanding the changes in the field-performance properties of a carbonate reservoir caused by fluid movements during hydrocarbon extraction in producing fields. The aim of this work is to better understand and quantify the dependence of elastic moduli and extensional attenuation on water saturation in a limestone sample. We present the results of laboratory measurements of moduli and extensional attenuation conducted on dry and water saturated Savonnieres oolitic limestone (permeability – 61 mD, porosity – 26%) at seismic frequencies of 1 Hz and 10 Hz. We observed a gradual decrease of the Young and bulk moduli of the sample with increase of water saturation which changed to a growth at 100% saturation. The shear modulus was gradually decreasing until the complete saturation was attained. We also demonstrated that for nonzero water saturation the measured bulk moduli are below the moduli predicted by the Gassmann-Wood model.